Impact of probiotic and prebiotic on gut microbiota in pre-diabetes and type 2 diabetes - Ramos, Fernanda Maria Manzini [UNESP]; Salgaço, Mateus Kawata [UNESP]; Cesar, Thais [UNESP]; Sivieri, Katia [UNESP] (Springer Nature, 2022)
The increased worldwide prevalence of pre-diabetes and diabetes, especially type 2 diabetes, requiring different strategies for their prevention and management. A new focus is the reversal of diabetes dysbiosis, a disruption of gut microbiota homeostasis, which is closely related to elevated blood glucose levels and altered metabolic parameters. In this sense, a balanced diet plays a key role, and, particularly, probiotic and prebiotic have shown a promising role. This chapter explored current knowledge on the potential of probiotic and prebiotic to modulate glucose homeostasis. We showed that the consumption of probiotics and prebiotics is a promising strategy with a beneficial impact on gut microbiota and glycemic control. Furthermore, specific probiotic strains, such as L. acidophilus, L. casei strain Shirota, and B. lactis Bb12, have demonstrated the ability to improve parameters related to pre-diabetes and type 2 diabetes. In addition, polyphenols are emerging as a new alternative in glycemic control through the production of short chain fat acids (SCFA) and decreased lipopolysaccharides (LPS) translocation that leads to metabolic endotoxemia. Finally, the ingestion of beneficial bacteria, and foods rich in fiber and polyphenols, or a combination of them, is a good strategy for the control of pre-diabetes and type 2 diabetes, but more studies are still needed, mainly clinical trials, for these strategies are improved and widely used.